Head-content or headcount? Short-term skilled labour movements as a source of growth - Massimiliano Tani (Institute for the Study of Labor (IZA), 2006)
This paper contributes a theoretical model to study the effects of short-term movements of skilled labour on a country's economic growth. As traditional migration models emphasise the long-term effects of migration on factor endowments, they typically omit the analysis of gross labour flows. Gross flows however capture the volume of interactions and knowledge exchanges between workers living in different countries, which in turn affect the stock of knowledge available to their places of residences, and hence their ability to innovate and grow. A simulation based on available US, British and Australian data on international business visits reveals that short-term skilled labour movements have a positive and not insignificant effect on growth.
Keywords: F2; J6; 330; international migration; temporary labour movements; skilled labour; economic growth